Tannin: A natural corrosion inhibitor for aluminum alloys - Nardeli, Jéssica V. [UNESP]; Fugivara, Cecilio S. [UNESP]; Taryba, Maryna; Pinto, Elaine R.P. [UNESP]; Montemor, M. F.; Benedetti, Assis V. [UNESP] (Elsevier, 2019)
This work aims at investigating the effect of tannin, a natural compound, as corrosion inhibitor for bare and coated aluminum alloys (AA1200). Tannin was characterized by Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (FTIR-ATR) and its interaction with the sample surface was evaluated by computational calculations using the density functional theory (DFT) and electrochemical measurements. The corrosion behavior was studied by open circuit potential (EOCP), electrochemical impedance spectroscopy (EIS) and by the scanning vibrating electrode technique (SVET). Complementary studies were performed by scanning electron microscopy (SEM). Results demonstrated that tannin is an effective corrosion inhibitor protecting both coated and uncoated aluminum samples.
Keywords: AA1200 alloy; Coatings; Corrosion protection; Inhibitor; Tannin